IN VITRO ANTIMICROBIAL SCREENING OF AQUILARIA AGALLOCHA ROOTS - Canli, Kerem; Yetgin, Ali; Akata, Ilgaz; Altuner, Ergin Murat (African Traditional Herbal Medicine Supporters Initiative (ATHMSI), 2016)
Background: It was previously shown that some parts of Aquilaria agallocha, which is commonly known as oud or oodh, such as roots have been used as a traditional medical herbal in different countries. In Turkey A. agallocha is one of the ingredients while preparing famous Mesir paste, which was invented as a medicinal paste and used from the Ottoman period to now at least for 500 years. The identification the in vitro antimicrobial activity of ethanol extract of A. agallocha roots is main purpose of this analysis. Materials and Methods: By using 17 bacteria and 1 fungi, which include Bacillus, Candida, Enterobacter, Enterococcus, Escherichia, Klebsiella, Listeria, Pseudomonas, Salmonella and Staphylococcus genera, the activity of A. agallocha root extracts were analysed by the help of the disk diffusion method, that is one of the methods commonly used to determine antimicrobial activities. Results: As a result of the study it was observed that ethanol extracts of A. agallocha roots have a clear antimicrobial activity against nearly all microorganism used in the study, but only two bacteria namely E. coli ATCC 25922 and S. typhimurium SL 1344. Conclusion: According to the disk diffusion test results it may be possible to propose that A. agallocha roots should have a medicinal uses especially against E. faecium, L. monocytogenes ATCC 7644, B. subtilis DSMZ 1971, C. albicans DSMZ 1386, S. epidermidis DSMZ 20044 and S. aureus ATCC 25923.
Keywords: Antimicrobial screening; Mesir paste; Aquilaria agallocha, Mesir paste, antimicrobial activity, antimicrobial screening, ethanol extract; Bacteria; Ethanol; Turkey; Plant Extracts; Aquilaria agallocha; Ethanol extract; Microbial Sensitivity Tests; Antimicrobial activity; Plant Roots; Article; Anti-Infective Agents; Thymelaeaceae; 2. Zero hunger; 3. Good health